2006
DOI: 10.1002/syn.20258
|View full text |Cite
|
Sign up to set email alerts
|

Effect of monoamine oxidase inhibition on amphetamine-evoked changes in dopamine receptor availability in the living pig: A dual tracer PET study with [11C]harmine and [11C]raclopride

Abstract: The activity of both isozymes of monoamine oxidase (MAO) is reduced by 50% in the brain of human smokers. We hypothesized that this is not an epiphenomenon, but should bring about potentiation of the action of psychostimulant drugs. To test this hypothesis, we carried out serial positron emission tomography (PET) studies in Göttingen miniature pigs to measure the binding of the MAO-A ligand [11C]harmine and to measure the changes in [11C]raclopride binding evoked by a low dose of amphetamine (0.7 mg/kg as free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 57 publications
3
26
1
1
Order By: Relevance
“…); only the locus coeruleus and interpeduncular nucleus had higher MAO‐A binding in that study; we have earlier discerned [ 11 C]harmine binding in the locus coeruleus of living pigs (Jensen et al . ), but this was not evident in the present [ 18 F]FEH study, presumably because of greater effects of partial volume with μPET. The rank order and magnitude of present autoradiographic findings in vitro in cerebellum, striatum, and cerebral cortex match closely the results obtained earlier with [ 14 C]clorgyline, the irreversible ligand.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…); only the locus coeruleus and interpeduncular nucleus had higher MAO‐A binding in that study; we have earlier discerned [ 11 C]harmine binding in the locus coeruleus of living pigs (Jensen et al . ), but this was not evident in the present [ 18 F]FEH study, presumably because of greater effects of partial volume with μPET. The rank order and magnitude of present autoradiographic findings in vitro in cerebellum, striatum, and cerebral cortex match closely the results obtained earlier with [ 14 C]clorgyline, the irreversible ligand.…”
Section: Discussioncontrasting
confidence: 69%
“…); in brain of living pigs, this tracer had a V D close to 40 mL/g and a BP ND as high as three (Jensen et al . ). Recent clinical research PET studies with [ 11 C]harmine have revealed an association between MAO‐A and depression (Chiuccariello et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The most successful ligands which have been validated in humans are [ 11 C]harmine (e.g., Bergström et al 1997;Ginovart et al 2006;Jensen et al 2006;Soliman et al 2011), [ 11 C]clorgyline and [ 11 C]clorgyline-D2 (Fowler et al 1987Logan et al 2002) and [ 11 C]befloxatone (Bottlaender et al 2003;Leroy et al 2009). Another promising carbonlabeled PET ligand, …”
Section: Monoamine Oxidase Type a (Mao-a)mentioning
confidence: 99%
“…11 C]Harmine has as well been used in a dual tracer positron emission tomography (PET) study together with [ 11 C]raclopride in pig 10 and its biodistribution and radiation dosimetry evaluated in baboons. 11 Recently we observed that the high expression of MAO-A could be exploited for characterization of neuroendocrine gastroenteropancreatic tumours by using [ 11 C]harmine as a tracer.…”
Section: Introductionmentioning
confidence: 99%